Use of relatively located microearthquakes to map fault patterns and estimate the thickness of the brittle crust in Southwest Iceland. Sub-surface fault mapping in Southwest Iceland - Sigurlaug Hjaltadóttir 1976- (2009)
Verkefnið var unnið á Veðurstofu Íslands og var að miklu leyti hluti af Evrópusamstarfsverkefninu PREPARED, yfirverkefnisstjóri var Ragnar Stefánsson. The two rift zones in southern Iceland, the western and the eastern volcanic zones, are connected by an approximately 70 km long and 15 km wide left lateral shear zone, the South Iceland seismic zone (SISZ). Approximately every 100 years a sequence of large earthquakes of magnitudes M 6-7 occurs in the zone and traces of many Holocene faults have been mapped on the surface. Although the trend of the zone is east-west, major earthquakes take place on north-south striking faults, which leads to “bookshelf” type faulting. In June 2000, two large earthquakes of magnitudes ML6.4 and ML6.5 struck in the SISZ, three and a half days and approximately 17 km apart. Seismicity greatly increased in all Southwest Iceland and during 2000, roughly nineteen thousand microearthquakes were recorded there. The aim of this research is to relocate the earthquakes using a double- difference relative location method and to map the faults that they occur on. Due to the high clock-accuracy of the Icelandic SIL seismic network, the method can, through cross- correlation, reduce the uncertainties in relative arrival times and thus increase relative location accuracy to as far as tens of meters. This enables fault mapping by grouping together relocated events that form apparent lineaments. A suite of possible mechanisms are calculated for each event based on polarities and spectral amplitudes. Through the joint interpretation of fault mechanisms with the event distribution defining the fault, the slip direction on the fault plane can be inferred. Using this kind of mapping, about 240 faults, fault segments and small clusters, which were active in year 2000, have been mapped during this research. A detailed image of the two large fault planes of the 17 June event (J17) and the 21 June event (J21) has been revealed. The aftershock activity on the 12.5 km long, 10 km wide, north-south ...